DISTRIBUIÇÃO POTENCIAL DA CANELA-LOURO, Nectandra megapotamica (SPRENG.) MEZ, NO BIOMA MATA ATLÂNTICA - FERNANDES, Maria Eduarda Gomes,; SOUZA, Beatriz Cristina de Paula,; BAILLY, Dayani,; DELCONTE, José Hilário,; SILVA, Ana Francisca Gomes,; BATISTA-SILVA, Valéria Flávia, (ANAIS DO ENIC, 2024)
-